Swimming process of a child diagnosed with autism spectrum disorder: action research. (Revista horizonte, 2015)
To identify the driving force benefits that can be achieved with swimming in a child with syndrome of the autistic spectrum an action-research methodology was used with a two-year and six months old subject, who was given an individualized process for five months, incorporating as central axis the principle of variability with the purpose to break the traditional training patterns for people with autism. The driving force responses were identified every fourth session through a table of comparison, and in weekly analyses by the research team. The tables of comparison determined that swimming promotes the force development of the child. Some progress was identified in the responses of the child in the aquatic environment, which enable him to perform better in the social world.